Design of polyurethane fibers: Relation between the spinning technique and the resulting fiber topology - Tan, Chin Joo; Lee, Jacky Jia Li; Ang, Bee Chin; Andriyana, Andri; Chagnon, Grégory; Sukiman, Muhamad Shafiq (Wiley, 2019)
Properties or characteristics of fibers are affected by their topology. In fact, these topologies are found to have significant impacts in the functionalities of many applications. Hence, in this study, the relations between the spinning techniques and the topology of the resulting fibers are studied with the aim to provide a guideline for future reference where fibers with certain topology can be fabricated to suit specific applications. For this purpose, polyurethane is chosen to be the raw material to fabricate the fibers due to its versatility to be applied in various fields. The surface morphology, structures, and alignments of the fibers are studied. It is found that the polymer solution properties largely influence the mechanisms in the spinning process and can significantly affect the topology of the fibers. For instance, viscous solutions enable the spinning of coiled and smooth fibers, whereas conductive solutions encourage the splaying of the solution jet which results in the spinning of straight fibers. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 47706. © 2019 Wiley Periodicals, Inc.